New Methods of Reconstruction for Old Challenges: The Use of the Integra Graft in Necrotizing Soft Tissue Infections of the Male Genitalia. (7th October 2021) - Mitchell, Katharina; Crigger, Chad; Morley, Chad; Barnard, John; Dumasius, Vidas
Abstract : In this paper, we describe two cases of Fournier's gangrene (FG) in which Integra grafting was used for reconstruction. FG is a progressive necrotizing infection occurring in the perineal region and on the external genitalia. Reconstructive options using local tissue are limited due to the destruction this infection imposes on the soft tissue. Integra graft is a bilaminate artificial dermis made of shark chondroitin 6-sulfate and bovine collagen. It is applied to the wound bed after debridement and establishment of a healthy, well-vascularized wound base. The patients in this case series had large defects which could not be closed primarily with tissue beds and would not have been appropriate for skin grafting. Therefore, an Integra graft was placed. In both patients, the wound beds were appropriate for skin grafting after three weeks. Without the Integra graft, both of our patients would have needed to wait a considerable amount of time prior to reconstruction. Our case series further illustrates and supports the use of Integra grafts in such a scenario following Fournier's gangrene which has only previously been published on three occasions, all of which demonstrated successful outcomes.